The density of calcified plaques and the volume of calcium predict mortality in hemodialysis patients. (July 2016) - Bellasi, Antonio; Ferramosca, Emiliana; Ratti, Carlo; Block, Geoffrey; Raggi, Paolo
Abstract: Background and aim: In the general population lipid-rich plaques are prone to rupture and healing of the plaque involves calcification. Patients undergoing hemodialysis have a severe derangement of mineral metabolism and calcification of the arterial tree may have different implications. Methods: Between 2004 and 2005, 125 hemodialysis patients (60 men) underwent computed tomography imaging for quantification of coronary artery calcium via the Agatston and the Volume methods. Since the Agatston score is derived by multiplying the density by the volume of a calcified lesion, the Agatston/Volume ratio (AVR) is an indication of the density (i.e. calcium accumulation) within the plaque. Results: Patients were classified as high AVR (>1) or low (≤1) AVR. Survival analyses tested the association between AVR and all-cause mortality during a median follow-up of 5 years. The mean age was 57.2±13.5 years; 75% of the patients had AVR >1. The mortality rate of patients with AVR >1 was significantly higher than in patients with AVR ≤1 (Hazard Ratio(HR): 2.46; 95% Confidence Intervals(CI): 1.16–5.21, p ≤0.018). After adjustment for confounders, AVR >1 remained independently associated with all-cause mortality (HR: 2.24; 95% CI: 1.02–4.88, p ≤0.042). There was a significant interaction of plaque density and calcium volume on mortality. Conclusions: Increased plaque density is an independent predictor of all-cause mortality in hemodialysis patients. These data suggest that increased calcium content in the coronary arteries of patients in dialysis is an index of high-risk rather than a marker of plaque stabilization. Highlights: Patients on dialysis develop extensive vascular calcification. Calcium based binders are used to chelate phosphate. Calcium salts induce accumulation of calcium in the vessel wall. High plaque density predicts mortality in dialysis.